Da vila operária à região metropolitana: uma análise sobre Ipatinga (MG) - Silva, Moizés Rodrigues da (2020)
Ipatinga is a municipality located in the Vale do Rio Doce, state of Minas Gerais, east of the capital of Minas Gerais and belongs to the Metropolitan Region of Vale do Aço. Its urban space has an intrinsic relationship with the implantation of Usiminas (1956), a steel company, that gave rise to it as a company-city projected along the lines of an open city. The installation of the industry provided rapid changes in the urban space of Ipatinga, especially from the 1970s, when there was an accelerated population growth coupled with an urban expansion along the lines of peripheral urbanization. In this sense, the objective of the research was to understand the production of the urban space of Ipatinga from the urban plan in the context of contemporary urbanization, considering the constitution of the Metropolitan Region of Vale do Aço (MRVA) and its regional significance through flows of health, education and trade. We concluded that this process triggered spatial contradictions in Ipatinga, at the same time that the city was planned, there was a “spontaneous” occupation in areas of the municipality, thus generating an uneven occupation of space. From this work we came to the conclusion that the area of influence and the flows established by the city of Ipatinga and its importance in its immediate region, there is a greater role of this municipality in relation to the others that make up its network of influence. The territorial dynamics demonstrated based on the flows established by the recent studies of REGIC (2018), showed that Ipatinga established a significant dynamic of displacements due to health, education and trade / services with the municipalities of RMVA and Colar Metropolitano. The city is characterized as a Regional Capital - Level C, where it has a good management capacity as well as a regional influence. The plans did not lead to urban dispersion, but made it possible for socio-spatial inequalities to occur in intra-urban dynamics, being further increased in the municipalities of the Metropolitan Necklace.